ANALYSIS OF STEMFLOW, THROUGHFALL, AND INTERCEPTION ON BINTARO (Cerbera manghas), BUNGUR (Lagerstroemia speciosa) AND MERANTI (Shorea selanica) IN HALIM PERDANA KUSUMA URBAN FOREST, JAKARTA - ASTU WIDYANTI - Nim: 11513025 , LIDYA
Rainfall in a vegetation will be intercepted partly by the vegetation canopy as an interception water, partially evaporated into the atmosphere, and partly falling to the forest floor as a throughfall. The part intercepted by the leaf surface will flow through the stem towards the ground as a stem flow. Differences in tree species affect the amount of water distributed to the flow of stems, crown headings and interception, and then the rate of surface flow on a field. The lack of a scientific study of forest hydrology, particularly related to the ability of forest to reduce the impact of excessive surface flow, is the basis for this research. The objective of the study was to compare three species of trees, namely bintaro (Cerbera manghas), bungur (Lagerstroemia speciosa) and meranti (Shorea selanica) in terms of water interception, stem flow, and throughfall. The results of this study can be used as a consideration in the selection of suitable tree species to be planted in the urban forest of Jakarta, as well as enriching information about interception, stem flow, and throughfall of forest plant species. The research was conducted at Halim Perdana Kusuma City Forest, Jakarta, on January 13-February 3, 2017. Measurements were carried out on three tree species (bintaro, bungur and meranti), each repeated three times to obtain nine observation units. The rain observation period was conducted for 14 days. Based on the result of research, the largest stem flow value was found on meranti tree, 0,0051 mm (0.034% of rainfall), then bungur 0,0037 mm (0.025%) and the smallest was bintaro tree, 0,00295 mm 0.02%). The largest throughfall was found in bungur tree, 10,24 mm (69,65%), then meranti tree 9,03 mm (61,39%) and the smallest was bintaro tree, which was 7,85 mm (53,4%). The largest intercept value was in bintaro tree, 6.85 mm (46.57%), then meranti tree 5.67 mm (38.57%) and the smallest in bungur tree 4.46 mm (30.32% ). According to Irmas (2010), trees with the smallest throughfall and the highest interception value are the best trees. Thus, among the three tree species compared in this study, bintaro is the best tree that can be recommended for urban forest planting. The value of interception in Halim Perdana Kusuma city forest can be maximized by redesigning urban forest through silvicultural engineering aspects, planting pattern, facilities, vegetation selection, and nutrient input.